Investigating the Spillovers and Connectedness Between Green Finance and Renewable Energy Sources - Dogan, Eyup; Madaleno, Mara; Taskin, Dilvin; Tzeremes, Panayiotis (Pergamon-Elsevier Science Ltd, 2022)
Although a few studies have analyzed the nexus of renewable energy and green finance, the literature lacks the use of renewable energy by sources. The other major failure is that it uses only annual and small data. Therefore, this study investigates the connectedness and spillovers relationship between green finance and five types of renewable energy (biofuels, fuel cell, geothermal, solar, and wind) by applying the novel TVP-VAR method of Balcilar et al. [1] to the daily indexes from July 31, 2014, to Feb 4, 2022. The results show that dynamic connectedness, both total and pairwise, is heterogeneous over time and influenced by economic events. Furthermore, wind is found to be the largest transmitter of shocks to green finance, followed by biofuels, while both fuel cell and geothermal receive the least shocks. The findings suggest that green finance is mostly a net receiver of shocks from renewable energy sources and that wind has been a net receiver of shocks during the COVID-19 pandemic. A high interconnectedness between the indexes highlights the safe-haven property for diversification purposes of green finance. Our results are important for energy policymakers, those responsible for the implementation of environmental policies, individual investors, and portfolio managers, while also shedding light on the achievement of COP26 goals.
Tzeremes, Panayiotis/0000-0002-0746-3839; Taskin, Dilvin/0000-0001-6139-8006; Madaleno, Mara/0000-0002-4905-2771
Keywords: Green Finance; Renewable Energy; Connectedness; Tvp-Var